Draft Annual Plan 1988-89 Vol-II Government of Tripura - Planning Commission (Planning Commission, 1988)
monsoon rainfall, there was fluctuation in the production of different crops during the initial years of the plan mainly due to natural calamities associated with the vagaries of monsoon. There was sever flood condition during May-June, 1985 causing large scale damage to different Kharif crops. Again in August- September, 1985; winter paddy suffered seriously due to wide spread attack of rice hispa. During 1986 - 87, the rainfall was most erratic and drought situation prevailed upto June, 1986 affecting summer paddy and Rabi crops of 1985 - 86 and autumn paddy of 1986.
Government of Tripura